Decoding the Architectural Geometry of Plaosan Temple: An Ethnographic Exploration for Contextual Mathematics Education - Michelia Putri, Karolyne; Ishartono, Naufal (Jurnal VARIDIKA, 2026)
Student Many ethnomathematical studies in Indonesia have explored mathematical concepts embedded in cultural products such as batik, traditional houses, and other temple architectures. However, there has been little to no research specifically investigating the geometric aspects of Plaosan Temple as a cultural heritage site. Therefore, the current study aims to explore the geometrical concepts embedded in Candi Plaosan using an ethnographic approach. The study used ethnography as an approach by answering four principal questions, namely, "Where do I start looking?", "how do I find it?", "how do I recognize that it has found something significant?", and "how to understand what it is?". By answering these questions, the researchers successfully examined the geometrical concepts contained in Plaosan Temple. This study reveals that the concepts embedded in Plaosan Temple are focused on the geometrical aspect, namely, (1) plane geometry such as squares, rectangles, rhombuses, right triangles, trapezoids, and circles; (2) solid geometry such as cubes, rectangular prisms, and triangular prisms; (3) geometric transformations such as dilation and reflection; and (4) symmetry, similarity, and congruence. The findings are expected to introduce Plaosan Temple to students through contextual mathematics learning while supporting its preservation as cultural heritage. Future studies may further examine the effectiveness of Plaosan Temple–based learning with GeoGebra in enhancing students’ understanding of geometry concepts.